Validity of the Global Physical Activity Questionnaire in Older Adults With Chronic Obstructive Pulmonary Disease: Results From the National Health and Nutrition Examination Survey. Issue 4 (October 2020) - Gore, Shweta; Goldberg, Allon; Huang, Min H.; Shoemaker, Michael; Blackwood, Jennifer
Abstract : Purpose: The Global Physical Activity Questionnaire (GPAQv2) is widely used and one of the only national surveillance measures recommended by the World Health Organization for physical activity (PA) assessment globally. No studies to date have examined the validity of GPAQv2 in older adults with chronic obstructive pulmonary disease (COPD). This observational study examined its construct validity using population-based data. Methods: Individuals aged 65 years and older with COPD, interviewed in the National Health and Nutrition Examination Survey (NHANES) between years 2007 and 2012 were included. GPAQv2-derived PA was compared with constructs of lung function, shortness of breath, and the diagnosis of COPD. Results: The GPAQv2 was not found to be a significant predictor of COPD status (odds ratio = 1.00, 95% confidence interval: 0.99, 1.00) when controlling for relevant covariates. Age and smoking status emerged as the strongest predictors of COPD. Total PA was neither significantly associated with shortness of breath nor lung function. Conclusions: Older adults with chronic conditions such as COPD represent a unique subset of population discrete from the healthier counterparts. Given the importance of GPAQv2 as the only widely accepted population surveillance tool, future studies exploring its validity in this subset of individuals with COPD using different constructs and objective reference standards are needed.